2017
DOI: 10.1021/acssuschemeng.6b03123
|View full text |Cite
|
Sign up to set email alerts
|

Highly Biodegradable and Tough Polylactic Acid–Cellulose Nanocrystal Composite

Abstract: Poly­(l-lactide) cellulose nanocrystals-filled nanocomposites were fabricated by blending of cellulose nanocrystals-g-rubber-g-poly­(d-lactide) (CNC-rD-PDLA) and commercial PLLA, in which CNC-g-rubber was synthesized by ring opening polymerization (ROP) of d-lactide and a ε-caprolactone mixture to obtain CNC-P­(CL-DLA), followed by further polymerization of d-lactide to obtain CNC-rD-PDLA. X-ray diffraction (XRD), nuclear magnetic resonance (NMR), and solubility tests confirmed successful grafting of the rubbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
109
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 46 publications
(105 reference statements)
3
109
0
2
Order By: Relevance
“…18 Among nanoparticles generally, cellulose nanocrystal (CNC) is known for its superior mechanical properties, low cost, low density, abundance and renewability and is a promising candidate for generating new materials. [19][20][21][22] In recent years, numerous studies have been undertaken to prepare CNC nanocomposites employing melt mixing, solvent casting, or a combination of both. 2,[23][24][25][26][27][28][29][30][31] For example, recently, Dhar et al 29,30 demonstrated a single step reactive extrusion of PLA/CNC nanocomposites with improved processability, recyclability, and potential application for food packaging.…”
mentioning
confidence: 99%
“…18 Among nanoparticles generally, cellulose nanocrystal (CNC) is known for its superior mechanical properties, low cost, low density, abundance and renewability and is a promising candidate for generating new materials. [19][20][21][22] In recent years, numerous studies have been undertaken to prepare CNC nanocomposites employing melt mixing, solvent casting, or a combination of both. 2,[23][24][25][26][27][28][29][30][31] For example, recently, Dhar et al 29,30 demonstrated a single step reactive extrusion of PLA/CNC nanocomposites with improved processability, recyclability, and potential application for food packaging.…”
mentioning
confidence: 99%
“…Polimer-polimer sintesis seperti poliasam laktat (PLA), polihidroalkanoat (PHA), polivinil alkohol (PVA), dan polibutilena suksinat (PBS) merupakan polimer sintesis yang bersifat biodegradable. Polimer-polimer ini bersifat biocompatible dan mudah diproses serta tidak berbahaya ketika terdegradasi ke alam [1,2,3]. Penggunaan PLA sebagai pengemas memiliki kelebihan selain sifatnya yang tidak hanya biodegradable tetapi juga nontoksik karena banyak digunakan dalam bidang biomedis dan nilai kekuatan tariknya yang sebanding dengan polipropilena dan polietilena.…”
Section: Penggunaanunclassified
“…Penggunaan PLA sebagai pengemas memiliki kelebihan selain sifatnya yang tidak hanya biodegradable tetapi juga nontoksik karena banyak digunakan dalam bidang biomedis dan nilai kekuatan tariknya yang sebanding dengan polipropilena dan polietilena. Namun, kelemahan dari PLA ini adalah kerapuhannya yang tinggi dengan nilai elongasi 4-7% dan kekuatan impaknya hanya sekitar 2,6 kj/m2 [3].…”
Section: Penggunaanunclassified
“…Nowadays, many studies about bio‐based polymers have begun in the last decade due to an increasing environmental awareness and the depletion of oil resources . Specially, sustainable materials with high‐performance or biodegradability have become the research hot spot, such as poly(ethylene 2,5‐furandicarboxylate) (PEF), poly(1,4‐butylene 2,5‐furandicarboxylate), poly(lactic acid), and poly(butylene 2,5‐thiophenedicarboxylate) (PBTF) …”
Section: Introductionmentioning
confidence: 99%